Development of Local Culture-Based Image Media to Improve Student Learning Outcomes on the Material of Arithmetic Operations of Multiplication of Natural Numbers: Pengembangan Media Gambar Berbasis Kebudayaan Lokal Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Operasi Hitung Perkalian Bilangan Asli - Putri Tria Sundari; Sihabudin Sihabudin; Mansur Mansur (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The aim of this research is to develop Image Media learning media to calculate the multiplication of natural numbers for class II students at SDN Tejamari, Baros District. This research uses the type of research and development (R&D) from S. Thiagarajan's development model, which has 4 stages of development, namely defining, designing, developing and disseminating. The media developed is validated by material experts and media experts before conducting initial field trials on students. Data was collected using questionnaires from media experts, material experts, class II teacher questionnaires, student questionnaires, interview observations and documentation. Data resulting from research were analyzed using quantitative and qualitative analysis techniques. Based on the validation results, material experts got a score of 46 with a percentage of 83% with the criteria "Good", validation from media experts with a score of 44 with a percentage of 88% with the criteria "Very Good", and the results of class II teacher validation with a score of 99 with a percentage 94% with "Very Good" criteria. As for the results of the initial field trials, the percentage was 90% - 100% with the criteria "Very Good". Overall, the learning media Image Media is suitable for use by making it easier to calculate multiplication of natural numbers by students who have difficulty calculating multiplication using direct observation. This image media makes it easier for students to learn multiplication. Based on the results of the Pre-Test before using image media and the Post-Test using image media, the average score was 0.898 with high criteria. And obtained an N-Gain percentage score of 89.833 in the effective category. So, the learning media Image Media has been effectively used for students in improving learning outcomes for the arithmetic operation of multiplying natural numbers.